An Analysis of the Determinants of Commercial Banks Profitability in Malaysia - Khairul Anuar, Desa (2003)
The message is thus clear, which is even louder after the recent financial crisis of the banking sector in this region in 1997. Commercial banks in Malaysia will have to review the way they have been doing business in the past and they would need to understand the internal and external factors, which influence their profitability performance. Such an understanding of the dynamics of the operating relationships would not only be useful for sustaining high profitability but would also be essential for the surviva1 of these commercial banks by enabling them to hedge against the adversities of external shocks. The above factors may or may not have an impact on the profitability performance of the commercial banks. Many studies have been done to analyse the profitability performance of commercial banks around the world. Unfortunately, there has not been much study on the profitability performance of Malaysia commercial banks especially. For that reason, this study attempts to identify and try to measure the determinants of commercial banks profitability in Malaysia. In this study, linear regression analysis, which are commonly used for measuring a bank’s performance and profitability provided in financial management theories as well as banking regulators, have been applied in measuring the profitability of the Malaysian commercial banks. This study has emphasized on the profitability of capital ratio, bank size, base lending rate, gross domestic product, inflation, expenses management, interest coverage, total loan, total deposit and total income of the Malaysian commercial banks for a period of 11 years starting 1990 to 2000. Among the ten variables selected special for this study, six variables are found to be significance at 0.05, two of them is significance at the level of 0.10 and two variables are found insignificance to the dependent variable of profitability, ROA. Six variables significance at the level 0.05 is capital ratio (CR), bank size (SIZE), interest coverage (INC), total loan (LOAN), total deposit (DEPOSIT) and total income (TI). Two variables significance at the level 0.20 is gross domestic product (GDP) and inflation rate (INFL). Another two variables are found insignificance for this study is base lending rate (BLR) and expenses management (EXPS).